MANAGING CHANGES AT A CATERING BUSINESS (Journal of Media studies, 2020)
This article analyzes management approaches and decisionsof a public catering establishment in Almaty city, the Republic of Kazakhstan.The authors of the study used qualitative research methods in order to examinethe current situation and business processes of the object of the study. The modelof three-stage change process by Kurt Lewin was used as a theoretical basis, andsuch types of analysis as the affinity diagram, the stakeholder analysis, theinterrelationship diagram, and the Pareto diagram were used in order to interpretand understand challenges in the company functioning. The main objective ofthe article is to study the activities of the research object and offerrecommendations for improving its operational activities on the market. Theauthors of the article claim that changes must be managed, they also state that itis important to know how to manage successful changes.